Surfactants synthesis on the basis of secondary raw materials after waste treatment - Нікітченко, Юлія Станіславівна (Eastern-European Journal of Enterprise Technologies, 2014)
The scale of production of surfactants as one of the most popular products of petrochemical synthesis are determined by a number of factors, among which the availability of accessible and commercially attractive materials is the most important. For a long time, oleochemical and petrochemical products were used as raw materials, but today, because of the instability in the global market of raw materials, the issues of finding new and diversification of existing sources of raw materials become particularly relevant. One of such sources may become production and consumption waste, produced in large quantities in every country. It is globally recognized that resource-oriented consumption waste treatment can be a powerful source of secondary material-energy raw materials for many industries, including the petrochemical. In the paper, the possibility of using a narrow fraction of pyrolysis condensate that boils at a temperature above 350 °C and contains more than 50 % of aromatic hydrocarbons to synthesis anion-active surfactants was experimentally confirmed. Pyrolysis condensate is obtained during thermal processing of waste tires of vehicles which, at significant accumulation in the environment is an important factor of environmental hazards in all regions of Ukraine. For the synthesis of surfactants, technology of processing the mentioned fraction by sulfonation at 50–60 °C using SO3 as sulfonating agent and extraction of sulfonates by aqueous isopropanol solution is recommended. Composition and properties of the resulting product depend on the sulfonation conditions. All samples obtained are water-soluble. In order to confirm the practical significance of the results, the paper gives the results of using the synthesized product in compositions for cleaning oil-contaminated soils. The cleaning efficiency of soils is 85–90 %, which is not inferior to surfactants, based on traditional raw materials.